2021
DOI: 10.1101/2021.05.06.442886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimizing network neuroscience computation of individual differences in human spontaneous brain activity for test-retest reliability

Abstract: A rapidly emerging application of network neuroscience in neuroimaging studies has provided useful tools to understand individual differences in complex brain function. However, the variability of methodologies applied across studies - with respect to node definition, edge construction, and graph measurements- makes it difficult to directly compare findings and also challenging for end users to select the optimal strategies for mapping individual differences in brain networks. Here, we aim to provide a benchma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 171 publications
0
20
0
Order By: Relevance
“…Like most graph theoretical measures, the calculation of global efficiency requires a sparse graph to represent a biologically plausible network of functional connectivity 40 . Following recent work on the most reliable and representative construction of brain networks 33,40,41 , we calculated individual OMST based on the weighted functional connectivity matrices and used the OMST to assess global efficiency. A linear mixed-effects model indicated higher global efficiency for young adults ( x 2 = 21.86, p < 0.001; Figure 4d; Table S8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Like most graph theoretical measures, the calculation of global efficiency requires a sparse graph to represent a biologically plausible network of functional connectivity 40 . Following recent work on the most reliable and representative construction of brain networks 33,40,41 , we calculated individual OMST based on the weighted functional connectivity matrices and used the OMST to assess global efficiency. A linear mixed-effects model indicated higher global efficiency for young adults ( x 2 = 21.86, p < 0.001; Figure 4d; Table S8).…”
Section: Resultsmentioning
confidence: 99%
“…While threshold-based filtering methods like proportional or absolute thresholding are commonly applied in network neuroscience, they are driven by an arbitrary choice of the respective threshold and suffer from low reliability (Luppi and Stamatakis, 2021). To avoid these pitfalls and based on recent research on the reliability of graph construction in neuroscience (Jiang et al, 2021; Luppi and Stamatakis, 2021), we calculated the orthogonalized minimum spanning tree (OMST; Dimitriadis et al, 2017) on the weighted functional connectivity matrices. Apart from its high reliability, the OMST has several advantages compared to commonly applied threshold-based methods of graph construction: It adheres to the intrinsic topological structure of the brain network by resulting in a fully connected, weighted graph and offers a data-driven method of individualized network construction accounting for each individual’s optimal state of economic wiring in terms of cost and efficiency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that we adopted a robust dataset and included a replication section, methodological choices including MRI acquisition scheme, processing pipeline, network reconstruction, and group consensus algorithm may still be susceptible to false positives and negatives (Jiang et al, 2021;Korhonen, Zanin, & Papo, 2021;Maier-Hein et al, 2017;Sarwar, Ramamohanarao, & Zalesky, 2021). In particular, the deterministic tractography procedure yields relatively sparse connectomes and future work should consider the effect of connectome reconstruction and sparsity on the definition of polysynaptic FCs.…”
Section: Discussionmentioning
confidence: 99%
“…Construction of functional brain networks using OMST-based methods tends to increase the amount of between-subject variability when applied to functional brain networks (Jiang, Betzel et al 2021). However, our analyses comparing different parameter selections showed that for the network features we studied, the strongest relationships with episodic memory occurred when we reduced the variability in initial network construction (via thresholding edges by their frequencies) ( Figure S7 ).…”
Section: Discussionmentioning
confidence: 99%